Presidential Address: Historical Thinking, C.P. Snow’s Two Cultures, and a Hope for the Twenty-First Century - Gaffield, Chad (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 2001)
AbstractDuring the past thirty years, researchers have reconceptualized historical change within and across societies. At the time of the “new social history” in the 1960s and 1970s, scholars may have argued about method and the relative importance of “top-down” and “bottom-up” forces but they generally shared key assumptions about historical change including linearity, singularity, and simplicity. By the 1980s, however, historical thinking was becoming part of a campus-wide reconceptualization of change that emphasizes non-linearity, multiplicity, and complexity. An analysis of the discipline of History illustrates how this reconceptualization is laying the foundation for unprecedented horizontal connections of the humanities, social sciences, natural sciences, engineering, and biomédical fields. C.P. Snow's description of Two Cultures may still apply to many aspects of university life but the profound rethinking now underway in History and other disciplines points to the possibility of interconnected scholarly cultures.